2013
DOI: 10.1186/1532-429x-15-74
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique to quantify the instantaneous mitral regurgitant rate

Abstract: BackgroundThe systolic variation of mitral regurgitation (MR) is a pitfall in its quantification. Current recommendations advocate using quantitative echocardiographic techniques that account for this systolic variation. While prior studies have qualitatively described patterns of systolic variation no study has quantified this variation.MethodsThis study includes 41 patients who underwent cardiovascular magnetic resonance (CMR) evaluation for the assessment of MR. Systole was divided into 3 equal parts: early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…They concluded that there is significant variation of the mitral regurgitant rate even among patients with holosystolic MR jets and concluded that quantitative ways of assessing MR as suggested above via CMR effectively take into consideration this important confounding factor. A subsequent multicenter study determined that systolic variation is one of the factors that accounts for the discordance between echocardiographic and CMR assessment of MR, as the use of the color Doppler jet at a single point in time is the basis of many echocardiographic methods, and hence cannot factor in systolic variation 37,38 …”
Section: Imaging Protocols and Methodology For Assessment Of Mr Via Cmrmentioning
confidence: 99%
“…They concluded that there is significant variation of the mitral regurgitant rate even among patients with holosystolic MR jets and concluded that quantitative ways of assessing MR as suggested above via CMR effectively take into consideration this important confounding factor. A subsequent multicenter study determined that systolic variation is one of the factors that accounts for the discordance between echocardiographic and CMR assessment of MR, as the use of the color Doppler jet at a single point in time is the basis of many echocardiographic methods, and hence cannot factor in systolic variation 37,38 …”
Section: Imaging Protocols and Methodology For Assessment Of Mr Via Cmrmentioning
confidence: 99%
“…A subsequent multicenter study determined that systolic variation is one of the factors that accounts for the discordance between echocardiographic and CMR assessment of MR, as the use of the color Doppler jet at a single point in time is the basis of many echocardiographic methods, and hence cannot factor in systolic variation. (34,35)Qualitative assessment of mitral valve anatomy and MR: When assessing mitral valve anatomy, the anterior and posterior leaflets, the annulus, the subvalvular apparatus (papillary muscles), and LV contractility including any regional wall motion abnormalities, are carefully visually assessed and their pathophysiology is commented upon. Abnormal leaflet morphology includes thickening, calcification, redundancy, perforation, vegetations, other masses and clefts.…”
Section: Imaging Protocols and Methodology For Assessment Of Mr Via Cmrmentioning
confidence: 99%
“…The design of arterial phantoms has proved useful for modelling [ 57 ]. The application of CMR to the assessment of valvular heart disease continues to increase, [ 58 ] particularly in aortic stenosis [ 59 – 61 ]. This is in part due to greater appreciation of its complementary roles in relation to echocardiography, which is commonly the first line investigative technique.…”
Section: Atheroma Vascular Aorta Valvesmentioning
confidence: 99%